2016
DOI: 10.1177/0974686216666456
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Board Size and Firm Performance: Evidence from NSE Companies Using Panel Data Approach

Abstract: This article seeks to examine the relationship between the board size and firm performance. Existing literature on board size is based on different theories of corporate governance. While agency theory and resource dependency theory suggest that the board size positively affects performance, stewardship theory favours smaller board size and argues that larger board size negatively impacts the firm performance. The present article adds to the empirical literature by employing panel data analysis of 145 non-fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
78
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(103 citation statements)
references
References 36 publications
20
78
1
4
Order By: Relevance
“…Significant association exists between CEO duality and Tobin Q, and between CEO duality and ROE but in adverse mode. Same type of finding is revealed by Kalsie & Shrivastav (2016) where board opus and firm recital are statistically associated.…”
Section: Discussion Of Results Findingssupporting
confidence: 52%
See 2 more Smart Citations
“…Significant association exists between CEO duality and Tobin Q, and between CEO duality and ROE but in adverse mode. Same type of finding is revealed by Kalsie & Shrivastav (2016) where board opus and firm recital are statistically associated.…”
Section: Discussion Of Results Findingssupporting
confidence: 52%
“…Based on a study on Nairobi Securities Exchange, Ngulumbu & Aduda found the connection between board opus and financial recital; 'Corporate governance practice dictated the financial performance of listed organisations, uncovered that there was an expanding pattern inboard size, independent directors, number of board advisory groups, number of founder directors, gender-mix, level of training of executives and age of the executives over the three years. They finally concluded that the independent directors did an excellent job of predicting profitability' (2016:72)" Kalsie & Shrivastav (2016), in their study, examined the relationship between board composition and firm performance and stated that while stakeholder theory and agency theory suggest that board composition positively affects performance, other factors contribute to corporate performance and not only board composition. While Jensen, (1993:831) claims that; "good corporate structure provides firms with greater access to finance, lower cost of capital, improved performance and adequate treatment of all stakeholders likewise the shareholders."…”
Section: Empirical Review Of Corporate Governancementioning
confidence: 99%
See 1 more Smart Citation
“…Large boards may benefit firms in several ways, such as providing increases in firm value (Kalsie & Shrivastav, 2016) or a higher quality of financial reporting (Obigbemi, Omolehinwa, Mukoro, Ben-Caleb, & Olusanmi, 2016), among others. Thus, one of the attributes that makes boards effective in the sense of pressuring the management team to disclose CSR issues is their size (Jizi et al, 2014).…”
Section: Board Sizementioning
confidence: 99%
“…Dengan tingkat signifikansi 5 persen, ukuran perusahaan (firm size) yang dilihat dari logaritma total aset berpengaruh se cara negatif dan signifikan terhadap kiner ja perusahaan yang diproksikan oleh ROA dan ROTA. Sejumlah peneliti berargumen tasi bahwa ukuran perusahaan dan kiner ja perusahaan mempunyai pengaruh nega tif karena adanya disekonomis skala atau masalah agensi yang memburuk (Dang, Li, & Yang, 2018;Kalsie & Shrivastav, 2016;Vithessonthi & Tongurai, 2015;Yook, Choi, & Suresh, 2018). Adanya pengaruh nega tif antara ukuran perusahaan dengan kin erja menurut Belenzon & Patacconi (2014) dan Lahiri & Narayan (2013) terjadi karena adanya pemisahan kepemilikan dari mana jemen di perusahaan modern di mana tu juan manajer yang tadinya memaksimalkan keuntungan beralih ke tujuan untuk me maksimalkan utilitas manajerial.…”
Section: Hasil Dan Pembahasanunclassified